Bind to build: An interdisciplinary art project for learning of community development. Issue 2 (1st June 2013) - Ng-He, Carol
In Spring 2012, I brought my undergraduate course 'Arts and Community Development' at Columbia College Chicago outside of the classroom and into the community – Albany Park – a neighbourhood on Chicago's north side, known for its cultural and ethnic diversity. Building upon Chicago's nineteenth-century activism legacy of noted pioneer settlement worker and founder of the Hull-House, this essay presents the process of my students' art-based action research and creative workshop projects in an independently artist-run book-bindery, North Branch Projects, as a way of community engagement. The article will conclude with a personal reflection on the success of student-artist collaboration.